Pembelajaran Hybrid dalam Memfasilitasi Divergensi Kognitif Siswa Sekolah Dasar dalam Konteks Pembelajaran STEM - Magdalena, Ina; Nurcahyati, Aan; Zahranisa, Anida (Lembaga Yasin AlSys, 2023)
The purpose of this study is to evaluate the effectiveness of hybrid learning in facilitating cognitive divergence of elementary school students in the context of STEM learning. Hybrid learning is a teaching method that combines face-to-face and online learning. This study aims to explore the process of using hybrid learning in elementary schools and its impact on students' cognitive divergence. The study will use a qualitative research method with data analysis techniques using narrative analysis. The study will involve elementary school students in STEM learning programs. The study will evaluate the effectiveness of hybrid learning in facilitating cognitive divergence by comparing the learning outcomes of students who use hybrid learning with those who use traditional face-to-face learning. The study is expected to provide insights into the effectiveness of hybrid learning in facilitating cognitive divergence of elementary school students in the context of STEM learning.